Political Costs of Tax-Based Consolidations - Chen, Chuling (IMF Working Papers; Working Paper ;, 2019)
This paper studies the impact of tax-based consolidations on reelection outcomes. Using a granular database of tax-based consolidations for a panel of 10 OECD countries over the last 40 years, we find that tax reforms are politically costly but some reforms are costlier than others. Measures aimed primarily at reducing existing deficits and debt are costlier than tax consolidation policies for improving long-term growth prospects. Electoral costs are particularly high for broad-based indirect tax and corporate tax reforms. Voters tend to penalize governments less if tax consolidations are announced early in the government's term or if the government has a strong political mandate. Favorable economic conditions increase public support for tax-based consolidations. Personal income tax reforms are electorally salient if the reforms are frontloaded, announced during recessions, and in less progressive tax systems.